Contrail Formation: Analysis of Sublimation Mechanisms. Issue 24 (28th December 2018) - Kärcher, B.; Kleine, J.; Sauer, D.; Voigt, C.
Abstract: We study losses of ice crystals in a persistent, soot‐rich contrail in the wake behind a medium‐sized aircraft at cruise. Constraining a model covering ice nucleation, growth, and sublimation phases with an aircraft data set, we track the sublimation history over 2 min of contrail age and relate ice crystal numbers to the number of soot particles emitted by the aircraft engines. We analyze the observed vertical distribution of ice numbers, estimating an exponential scale height in the range 50–100 m and wake‐averaged ice numbers (1.3–1.7) × 10 15 (kg‐fuel) −1 after sublimation, removing 60% of the ice crystals that originally nucleated on emitted soot particles. We define soot emission‐ and ice supersaturation‐dependent contrail depths, affecting estimates of horizontal spreading rates of contrails. Our findings have ramifications for the representation of long‐lived contrails in global models. Plain Language Summary: Contrails are climate‐forcing agents, but their overall climatic effect is difficult to quantify. Airborne measurements quantify properties of the initially line‐shaped ice clouds forming behind cruising jet aircraft. Exploring the formation stage of contrails reveals something about their properties and enables us to predict how they evolve in the atmosphere. We elucidate processes in a contrail that remove within few minutes more than half of the ice crystals generated from the engine emissions. Ice crystal number in, and vertical extension of, young contrails are fundamental determinants of processes governing their life cycle and climate impact. Our results highlight the need for focused observational studies and pave the way for improvements in the representation of contrails and the clouds evolving from them in climate models. Key Points: We analyze the sublimation of contrail ice crystals in the aircraft wake vortex regime Wake‐average ice numbers increase with soot emissions despite significant sublimation losses Inhomogeneous vertical distributions of ice numbers affect processes controlling contrail life cycles